Parafuscosporella xishuangbannaensis sp. nov. (Fuscosporellales, Sordariomycetes) from submerged wood in China - Wang, Lin; Dong, Wei; Yang, Jun-Xian; Zhu, Rong; Zhang, Huang; Yu, Ze-Fen (Phytotaxa, 2023)
In this study, a novel lignicolous freshwater species, Parafuscosporella xishuangbannaensis, which was collected from Manfeilong reservoir in Xishuangbanna, Yunnan Province, China, is described and illustrated. The new species was established based on morphological characteristics and multi-locus phylogenetic analyses of combined LSU, SSU, ITS and rpb2 sequence data. Parafuscosporella xishuangbannaensis is characterized by reduced conidiophores, holoblastic, monoblastic, integrated, terminal, hyaline, cylindrical conidiogenous cells, and acrogenous, obovoid to subglobose, brown to dark brown conidia with a septum near the base and a paler, wedge-shaped basal cell. Parafuscosporella xishuangbannaensis differs from its phylogenetically close sister taxon P. pyriformis in lacking cylindrical or moniliform conidiophores.